1995
DOI: 10.1016/0014-5793(95)00977-h
|View full text |Cite
|
Sign up to set email alerts
|

Threading analysis suggests that the obese gene product may be a helical cytokine

Abstract: The ob gene encodes a protein that, in mutant form, is associated with obesity and type II diabetes in mice. Sequence analysis has revealed no similarities to other proteins, however, and no clues as to possible functions. The possibility nonetheless remains that ob is functionally or ancestrally related to other proteins, whose sequences are divergent to the point that only a comparison of three-dimensional structures might detect relationship. To explore this possibility, we conduct a 'threading' search of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0
10

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(139 citation statements)
references
References 41 publications
6
123
0
10
Order By: Relevance
“…This observation was consistent with a previous structural prediction indicating that the leptin protein would be expected to fold into a cytokine-like structure (30). The closest relatives of OB-R were gp130 (31), the G-CSF receptor (32), and the leukemia inhibitory factor receptor (33).…”
supporting
confidence: 91%
“…This observation was consistent with a previous structural prediction indicating that the leptin protein would be expected to fold into a cytokine-like structure (30). The closest relatives of OB-R were gp130 (31), the G-CSF receptor (32), and the leukemia inhibitory factor receptor (33).…”
supporting
confidence: 91%
“…First, although the cloning of the Ob gene revealed no significant se quence homology with any other known protein, com putational based research studies predicted that leptin displayed tridimensional characteristics of a four helix bundled cytokine, such as those that activate the JAK STAT pathway (Figure 1) (13). Moreover, the cloning of the OB-R gene reported towards the end of 1995 (12) revealed that leptin receptor shared sequence ho mology with gp130, the signal transducing unit of the IL 6 receptor that signals via the JAK STAT pathway.…”
Section: Molecular Mechanisms Of Leptin and Modulation Of Immune Cellsmentioning
confidence: 99%
“…The primary amino acid sequence of leptin indicated that it could belong to the long-chain helical cytokine family, 36,42 with members such as IL-2 and IL-12. The cytokine-like structural characteristic of leptin is implicative of its function in regulating immune response.…”
Section: Leptin Inflammation and Immune Responsementioning
confidence: 99%